THE ROLE OF THE SEKAR BUDAYA GROUP IN PRESERVING THE ART OF JARANAN CAMPURSARI IN SUKOSARI VILLAGE, SUKOWONO DISTRICT, JEMBER REGENCY IN 2010-2018 - Novita Sari; marjono marjono; kayan swastika (History Education, University of Jember, 2019)
Sekar Budaya Group is an art group which houses the jaranan campursari art in Sukosari village, Sukowono subdistrict, Jember Regency. The Sekar Budaya Group has 35 members and also has 44 social gathering members. Sekar Budaya Group houses several art forms which are encompassed by the name of jaranan campursari. In the show, the Sekar Budaya Group always presents the arts it fosters, known by the people of the jaranan campursari sukosari. The establishment of the Sekar Budaya Group was motivated by economic factors and the condition of the art jaranan. Efforts made by the Sekar Budaya Group in preserving the art of the campursari network include protection efforts, utilization efforts, and development efforts. The efforts made by the Sekar Budaya Group had a positive impact on the development of network art and member income. Keywords: Sekar Budaya Group, Jaranan Art Campursari